AVALIAÇÃO REPRODUTIVA DE FÊMEAS NELORES PRECOCES CONFINADAS - LIMA, Thais Ferreira; SANTOS, Caroliny Silva; PEDRO, Felipe de Oliveira; BAIACUE, Juan Sebastian Fuentes; SOUZA, Andréa Roberto Duarte; MELO-STERZA, Fabiana Andrade (ANAIS DO ENIC, 2025)
-